Thermoelectric material and method for manufacturing thermoelectric element
The described method addresses contamination and oxidation issues in Mg3Sb2 thermoelectric material production by using low-temperature heat treatment and pressure sintering, resulting in high-performance thermoelectric elements with reduced costs and environmental footprint.
Patent Information
- Application Number
- JP2021027091
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-24
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-02-24
AI Technical Summary
Conventional methods for manufacturing Mg3Sb2 thermoelectric materials face issues such as contamination, oxidation susceptibility, low mass productivity, and composition deviation due to high-pressure milling or high-temperature melting, which affect the thermoelectric performance and efficiency.
A method involving heat treatment of raw materials below the melting points of magnesium and antimony, followed by pressure sintering using a discharge plasma sintering method, with optional magnesium addition before sintering to maintain composition integrity, to produce Mg3Sb2 thermoelectric materials.
This method enables the production of high-performance Mg3Sb2 thermoelectric elements with improved thermoelectric properties and reduced manufacturing costs, while minimizing environmental impact and avoiding composition deviations.
Smart Images

Figure 0007610252000001 
Figure 0007610252000002 
Figure 0007610252000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a thermoelectric material and a thermoelectric element, and in particular to a method for producing an Mg3Sb2-based thermoelectric material and an Mg3Sb2-based thermoelectric element. [Background technology]
[0002] Magnesium antimony (Mg3Sb2)-based thermoelectric materials have been known for some time, with thermoelectric properties improved by incorporating various dopants into magnesium antimony (Mg3Sb2). Thermoelectric elements using Mg3Sb2-based thermoelectric materials are known to have relatively high thermoelectric performance (power generation performance).
[0003] Conventionally, Mg3Sb2-based thermoelectric materials have been produced by the mechanical alloying method using a ball mill (hereinafter referred to as the "MA method"), the melting method, or the like.
[0004] The MA method is a method for mechanically alloying starting materials by pulverizing and mixing them using a high-pressure ball mill such as a planetary ball mill. The alloy powder obtained by the MA method is sintered by a pressure sintering method such as hot press sintering or spark plasma sintering (SPS) before being used as a thermoelectric element.
[0005] However, the MA method uses a high-pressure ball mill, which can cause contamination problems due to material components such as balls. In addition, the specific surface area of the mixed powder is large in the MA method, which makes it prone to oxidation, and in order to prevent deterioration of the thermoelectric properties due to oxidation, it is usually necessary to work in a glove box with an inert atmosphere. Furthermore, the MA method has the problem of low mass productivity because the amount of powder that can be processed at one time is extremely small.
[0006] On the other hand, the melting method is a method for achieving alloying by melting the starting materials at high temperatures. The alloy obtained by the melting method is solidified, crushed into powder, and then sintered by pressure sintering, just like the MA method, for use as a thermoelectric element.
[0007] However, the melting method requires high-temperature heat treatment, which can lead to problems with compositional deviations due to the evaporation of some components.In addition, magnesium (Mg), the raw material for Mg3Sb2-based thermoelectric materials, has a high vapor pressure, so when the melting vessel is sealed, there is a risk of the vessel being damaged by the internal pressure.
[0008] In addition, WO 2017 / 72982 discloses the compound with the chemical formula Mg 3.07 Sb 1.47 Bi 0.53 A thermoelectric conversion material represented by the formula: [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2017 / 72982 (Paragraph 0030) Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a method for producing an Mg3Sb2-based thermoelectric material and an Mg3Sb2-based thermoelectric element that differs from conventional methods. [Means for solving the problem]
[0011] The method for producing a thermoelectric material according to the present invention includes a synthesis step of synthesizing an Mg3Sb2-based thermoelectric material by heat treating raw materials used in the synthesis of the Mg3Sb2-based thermoelectric material, and the synthesis step is characterized in that the heat treatment is performed at a temperature below the melting points of magnesium and antimony.
[0012] In this case, the raw materials may be magnesium and antimony, or the raw materials may be magnesium, antimony, and a dopant.
[0013] In the above case, the method may further include a weighing step of weighing the raw materials used in the synthesis of the Mg3Sb2-based thermoelectric material. 3+m Magnesium and antimony may be weighed out so that Sb2 (0≦m≦0.2) is satisfied.
[0014] In the above case, the method may further include a molding step of pressure-molding raw materials used in the synthesis of the Mg3Sb2-based thermoelectric material, and the synthesis step may include heat-treating the synthesis green body formed in the molding step to synthesize the Mg3Sb2-based thermoelectric material.
[0015] The method for manufacturing a thermoelectric element according to the present invention is characterized by comprising: a step of manufacturing an Mg3Sb2-based thermoelectric material by the method for manufacturing a thermoelectric material; and a sintering step of sintering the Mg3Sb2-based thermoelectric material.
[0016] In this case, the method may further include a crushing step of crushing the Mg3Sb2-based thermoelectric material synthesized in the synthesis step, and the sintering step may sinter the Mg3Sb2-based thermoelectric material crushed in the crushing step.
[0017] In the above case, the method may further include a magnesium adding step of adding magnesium to the Mg3Sb2-based thermoelectric material, and the sintering step may sinter the Mg3Sb2-based thermoelectric material to which magnesium has been added in the magnesium adding step.
[0018] In the above case, the sintering step may be performed by a pressure sintering method (for example, a spark plasma sintering method). Effect of the Invention
[0019] According to the present invention, it is possible to produce an Mg3Sb2-based thermoelectric material and an Mg3Sb2-based thermoelectric element by a method different from the conventional method. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram for explaining a method (first embodiment) for producing a thermoelectric material and a thermoelectric element according to the present invention. [Diagram 2] 5A to 5C are diagrams for explaining another method (second embodiment) for manufacturing a thermoelectric element according to the present invention. [Diagram 3] FIG. 2 is a cross-sectional view for explaining the configuration of a sintering jig used in the sintering step of the embodiment. [Figure 4] 1 is a table showing the evaluation results of each thermoelectric element. [Diagram 5] FIG. 2 is a diagram showing the X-ray diffraction patterns of each thermoelectric element (Examples 1 to 3). [Figure 6] FIG. 2 is a diagram showing the X-ray diffraction patterns of each thermoelectric material (Examples 1 to 3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.
[0022] The manufacturing method of a thermoelectric material and a thermoelectric element according to the present invention is for producing an Mg3Sb2-based thermoelectric material (Mg3Sb2-based alloy) and an Mg3Sb2-based thermoelectric element, and in the synthesis process of the Mg3Sb2-based thermoelectric material, a heat treatment is performed at a temperature lower than the melting point of magnesium (Mg) (648.8°C) and the melting point of antimony (Sb) (630.7°C) to cause a solid-solid reaction between magnesium and antimony.
[0023] It should be noted that the Mg3Sb2-based thermoelectric materials and Mg3Sb2-based thermoelectric elements referred to here include both those to which a dopant has been added and those to which no dopant has been added (thermoelectric materials and thermoelectric elements composed only of Mg3Sb2).
[0024] First Embodiment FIG. 1 is a diagram for explaining a method for producing a thermoelectric material and a thermoelectric element according to the present invention.
[0025] As shown in the figure, first, the raw materials are weighed (S1). For example, magnesium (Mg) powder and antimony (Sb) powder, which are the main raw materials, are weighed. If a dopant is added, the dopant is also weighed.
[0026] Next, the raw material powders are mixed so that the raw material powders weighed in the weighing step S1 become uniform (S2). For example, the raw material powders are mixed using a mixer or the like.
[0027] Next, the raw material powders uniformly mixed in the mixing step S2 are pressure-molded to produce a green body for synthesis (S3). For example, the green body for synthesis is produced by cold uniaxial pressing at an appropriate surface pressure (for example, about 20 MPa).
[0028] Next, the synthetic green body produced in the molding step S3 is heat-treated at a temperature below the melting points of magnesium and antimony to synthesize an Mg3Sb2-based thermoelectric material (S4). For example, the synthetic green body is placed in a semi-closeable container (e.g., a carbon container), and then placed in an electric furnace and held in an argon (Ar) atmosphere at a temperature of about 300 to 600°C (e.g., 450°C) for 3 hours or more to synthesize an Mg3Sb2-based thermoelectric material.
[0029] Next, the Mg3Sb2-based thermoelectric material synthesized in the synthesis step S4 is pulverized (S5) by, for example, an automatic mortar or a ball mill, so as to have a desired particle size (for example, 90 μm or less).
[0030] Next, the Mg3Sb2-based thermoelectric material pulverized in the pulverization step S5 is sintered (S6). In this embodiment, pressure sintering is performed by spark plasma sintering (SPS). For example, pressure sintering by SPS is performed under the conditions of a sintering pressure of about 20 MPa to 50 MPa, a sintering temperature of about 500 to 900°C, and a sintering time of about 2 to 30 minutes.
[0031] The sintered body manufactured through the above steps S1 to S6 is processed into a desired shape as necessary and then used as a thermoelectric element.
[0032] Second Embodiment Next, another method for producing a thermoelectric element according to the present invention (second embodiment) will be described.
[0033] 2 is a diagram for explaining a method for manufacturing a thermoelectric element according to a second embodiment of the present invention. In this embodiment, magnesium is additionally added in a step after synthesis of the Mg3Sb2-based thermoelectric material and before sintering. The additional addition of magnesium is performed to prevent composition deviation in the final thermoelectric element (sintered body).
[0034] In the following, only the differences from the first embodiment will be basically described. The same steps as those in the first embodiment will be denoted by the same reference numerals and detailed description thereof will be omitted.
[0035] As shown in FIG. 2, first, the raw materials are weighed (S1).
[0036] Next, the raw material powders are mixed so that the raw material powders weighed in the weighing step S1 become uniform (S2).
[0037] Next, the raw material powders uniformly mixed in the mixing step S2 are pressure-molded to produce a green body for synthesis (S3).
[0038] Next, the synthetic green body produced in the molding step S3 is heat-treated at a temperature below the melting points of magnesium and antimony to synthesize an Mg3Sb2-based thermoelectric material (S4).
[0039] Next, the Mg3Sb2-based thermoelectric material synthesized in the synthesis step S4 is pulverized (S5).
[0040] Next, magnesium (Mg) is added to the Mg3Sb2-based thermoelectric material pulverized in the pulverization step S5 (S21). In this embodiment, magnesium is added in an amount according to the degree of composition deviation at the stage of the Mg3Sb2-based thermoelectric material before sintering. The amount of magnesium added is determined, for example, based on the analysis results of the Mg3Sb2-based thermoelectric material manufactured under specific manufacturing conditions to be implemented.
[0041] Next, the Mg3Sb2-based thermoelectric material is mixed so that the Mg3Sb2-based thermoelectric material to which magnesium has been added in the magnesium addition step S21 becomes uniform (S22). For example, the Mg3Sb2-based thermoelectric material to which magnesium has been added is mixed using a mixer or the like.
[0042] Next, the Mg3Sb2-based thermoelectric material uniformly mixed in the mixing step S22 is sintered (S6).
[0043] The sintered body manufactured through the above-described steps S1 to S5, S21, S22, and S6 is processed into a desired shape as necessary and then used as a thermoelectric element.
[0044] Although the embodiment of the present invention has been described above, it is needless to say that the embodiment of the present invention is not limited to the above. For example, in the above-mentioned embodiment, pressure sintering is performed by the spark plasma sintering method (SPS) in the sintering step S6, but pressure sintering by other pressure sintering methods, for example, hot pressing method (HP) or hot isostatic pressing method (HIP), may also be performed. EXAMPLES
[0045] Next, examples of the thermoelectric material and the method for manufacturing a thermoelectric element according to the present invention will be described.
[0046] First, several types of thermoelectric elements made of magnesium antimony (Mg3Sb2) were produced by changing the starting composition as follows.
[0047] Example 1 First, magnesium (Mg) powder (manufactured by High Purity Chemical Laboratory Co., Ltd.) with a purity of 99.5% and an average particle size of 180 μm and antimony (Sb) powder (manufactured by Shanghai Chung-Fu Nam Technology Co., Ltd.) with a purity of 99.9% and an average particle size of 180 μm were weighed out so that the charged composition was Mg3Sb2.
[0048] Next, the raw material powders were mixed in a mortar until they were uniform. The raw material powders were then placed in a 30φ super steel die and pressed at a pressure of 20 MPa using a press (NT-50H, manufactured by NPA Systems Co., Ltd.) to obtain a cylindrical synthetic compact measuring 30φ x 3 mm.
[0049] Next, the obtained synthetic green body was placed in a semi-closeable carbon container with a lid, and then placed in an electric furnace, where it was first heated to 150°C in an argon atmosphere over 30 minutes, and then held at 150°C for 1.5 hours to evaporate the moisture in the synthetic green body. Next, the temperature was raised to 450°C at a rate of 200°C per hour (200°C / h) in an argon atmosphere, and held at 450°C for 3 hours to cause a solid-solid reaction between magnesium and antimony, resulting in a Mg3Sb2 thermoelectric material (ingot of Mg3Sb2 alloy).
[0050] Next, the obtained ingot was coarsely crushed in a mortar to a size of 1 mm or less, and then finely crushed in an automatic mortar (manufactured by Changzhou Zhongshi Sanshui Machinery Technology Co., Ltd., TYM120) to a particle size of 90 μm or less.
[0051] Next, the obtained Mg3Sb2 thermoelectric material powder was filled into a sintering jig as shown in FIG.
[0052] More specifically, a carbon sheet (manufactured by NJS Co., Ltd.) having a thickness of 0.2 mm was cut into a predetermined shape to prepare a cylindrical carbon paper 321 and upper and lower disk-shaped carbon papers (30φ) 322, 323. Next, the cylindrical carbon paper 321 was placed in a carbon die 311 having a diameter of 30.4φ, and then the lower carbon punch 313 was inserted. Next, the lower disk-shaped carbon paper 323 was placed on the lower carbon punch 313, and then the Mg3Sb2 thermoelectric material powder 301 was filled in. Next, the upper disk-shaped carbon paper 322 was placed on the Mg3Sb2 thermoelectric material 301, and then the upper carbon punch 312 was inserted.
[0053] The sintering jig 300 prepared as described above was placed in a spark plasma sintering apparatus (LABOX-1575, manufactured by Sinterland Co., Ltd.) and sintering was performed under conditions of a vacuum degree of 6 Pa, a sintering temperature of 550°C, a sintering pressure of 30 MPa, and a sintering time of 10 minutes to obtain a sintered body.
[0054] Next, the obtained sintered body was cut using a micro cutter (MC-201N, manufactured by Maruto Corporation) to cut out rectangular sintered body pieces of 15 mm×1.5 mm×1.5 mm to obtain the final thermoelectric element.
[0055] Example 2 First, the composition of the feed is Mg 3.2 The magnesium (Mg) powder and the antimony (Sb) powder were weighed out so as to obtain Sb2.
[0056] Thereafter, a thermoelectric element was produced in the same manner as in Example 1 described above.
[0057] Example 3 First, the composition of the feed is Mg 3.2 The magnesium (Mg) powder and the antimony (Sb) powder were weighed out so as to obtain Sb2.
[0058] Next, in the same manner as in Example 1 described above, a Mg3Sb2 thermoelectric material was synthesized, and the obtained Mg3Sb2 thermoelectric material was pulverized to obtain a powder of the Mg3Sb2 thermoelectric material.
[0059] Next, the obtained Mg3Sb2 thermoelectric material powder was mixed with the mixture of Mg 3.2 The above magnesium powder was added in an amount equivalent to Mg0.2 in Sb2 (the same amount as the amount charged in the weighing step).
[0060] Next, the Mg3Sb2 thermoelectric material powder to which the magnesium powder had been added was mixed in a mortar so as to be uniform, and then sintering was carried out in the same manner as in Example 1 described above to obtain a sintered body.
[0061] Next, the obtained sintered body was cut using the above-mentioned microcutter to cut out rectangular sintered body pieces of 15 mm×1.5 mm×1.5 mm to obtain the final thermoelectric element.
[0062] In addition, several types of thermoelectric elements were produced in the following manner, in which the manufacturing conditions (heat treatment temperature) in the synthesis process were different from those in the above Examples 1 to 3. More specifically, two types of thermoelectric elements were produced by setting the heat treatment temperature in the synthesis process to a temperature equal to or higher than the melting points of magnesium and antimony (specifically, 900°C).
[0063] Comparative Example 1 A thermoelectric element was produced in the same manner as in Example 1, except that the heat treatment temperature in the synthesis step was 900°C.
[0064] Comparative Example 2 First, the composition of the feed is Mg 3.1 The magnesium (Mg) powder and the antimony (Sb) powder were weighed out so as to obtain Sb2.
[0065] Thereafter, a thermoelectric element was produced in the same manner as in Example 1 described above, except that the heat treatment temperature in the synthesis step was set to 900°C.
[0066] Next, the produced thermoelectric elements were evaluated as follows.
[0067] First, one end of each thermoelectric element was heated with a heater, and when the temperature of that end reached a steady state of 28°C, the heater was turned off. Every time the temperature of that end dropped by 0.5°C, the temperature difference between the two ends and the output voltage were measured, and the Seebeck coefficient was calculated based on the measurement results.
[0068] The electrical conductivity was measured by the four-probe method, with the probe distances set to 1 mm and 2 mm, and the average of the two was used as the final measurement value.
[0069] Furthermore, based on the obtained Seebeck coefficient α and electrical conductivity σ, the power factor PF was calculated according to the following formula 1.
[0070] PF=α 2 σ (1)
[0071] Figure 4 is a table showing the evaluation results of each thermoelectric element. In the figure, α is the Seebeck coefficient (unit: μV / K), σ is the electrical conductivity (unit: S / m), and PF is the power factor (unit: μW / cmK 2 )
[0072] First, looking at the Seebeck coefficient α, as shown in the figure, all of Examples 1 to 3 and Comparative Examples 1 and 2 have positive values, indicating that they are p-type thermoelectric elements (p-type semiconductor elements).
[0073] Furthermore, comparing Examples 1 to 3, the Seebeck coefficient values of Examples 2 and 3 are smaller (half or less) than that of Example 1. Furthermore, the electrical conductivity σ values of Examples 2 and 3 are higher than that of Example 1.
[0074] That is, the more the amount of magnesium charged in the weighing step, the smaller the Seebeck coefficient and the higher the electrical conductivity. This is believed to be because in Examples 1 to 3, the heat treatment was performed at a low temperature (450°C) in the synthesis step, so the amount of magnesium evaporated in the synthesis step was small, resulting in a larger amount of simple metallic magnesium (which has a Seebeck coefficient of almost 0 and high electrical conductivity) remaining.
[0075] In addition, when Example 1 and Comparative Example 1, which have the same feed composition, are compared, Comparative Example 1 has a slightly smaller Seebeck coefficient value and a lower electrical conductivity than Example 1.
[0076] In addition, when the power factor PF is compared between Examples 1 to 3, the largest power factor FP is obtained in Example 1, which has the largest Seebeck coefficient value. Specifically, Example 1 has a power factor PF that is about three times larger than that of Example 2, and a power factor PF that is four times larger than that of Example 3.
[0077] In addition, when Example 1 and Comparative Example 1, which have the same feed composition, are compared, Example 1, which has a larger Seebeck coefficient and a higher electrical conductivity, has a larger power factor. In addition, when Example 1 and Comparative Example 2 are compared, Comparative Example 2 has a larger Seebeck coefficient, while Example 1 has a higher electrical conductivity, and finally, Comparative Example 2 has a slightly larger power factor PF.
[0078] From the above, it can be seen that the thermoelectric elements (Examples 1 to 3) produced by the method according to the present invention have thermoelectric performance (power factor PF) comparable to that of the thermoelectric elements (Comparative Examples 1 and 2) produced by the conventional method (melting method). In other words, according to the present invention, a thermoelectric element having thermoelectric performance (power factor PF) comparable to that of the conventional method (melting method) can be obtained by heat treatment at a lower temperature, which allows for reductions in manufacturing costs and carbon dioxide emissions during manufacturing.
[0079] In the process of producing each of the above thermoelectric elements, X-ray diffraction analysis was performed on the thermoelectric material powder before sintering and the sintered body after sintering. The X-ray diffraction analysis was performed using an X-ray diffractometer (MiniFlex600, manufactured by Rigaku Corporation) under the conditions of a tube voltage of 40 kV, a tube current of 15 mA, a scanning step of 0.02°, and a scanning speed of 25° / min.
[0080] 5 is a diagram showing the X-ray diffraction patterns of the sintered bodies of Examples 1 to 3. In the figure, from the top, the X-ray diffraction pattern of Example 1, the X-ray diffraction pattern of Example 2, and the X-ray diffraction pattern of Example 3 are shown. Furthermore, in the figure, the X-ray diffraction pattern of Mg3Sb2 transcribed from the JCPDS card data is also shown below the X-ray diffraction pattern of Example 3.
[0081] As shown in the figure, for Examples 1 and 2, peaks indicating the presence of elemental antimony are observed near 28.67° and 42.816°, and it is understood that the single phase of Mg3Sb2 is not formed, although slightly. On the other hand, for Example 3, in which additional magnesium was added before the sintering process, almost no peaks indicating the presence of elemental antimony are observed, and it is understood that the single phase of Mg3Sb2 is generally formed. In other words, by adding additional magnesium before the sintering process, it is possible to realize a single phase of Mg3Sb2 in the final sintered body.
[0082] 6 is a diagram showing the X-ray diffraction patterns of the thermoelectric material powders of Examples 1 to 3. In the figure, the X-ray diffraction pattern of Example 1, and the X-ray diffraction patterns of Examples 2 and 3 are shown from the top. Furthermore, in the figure, the X-ray diffraction pattern of Mg3Sb2 transcribed from the JCPDS card data is also shown below the X-ray diffraction patterns of Examples 2 and 3. Note that, for Examples 2 and 3, the X-ray diffraction patterns are the same at the stage of the thermoelectric material powder before the magnesium addition process, so they are shown as one X-ray diffraction pattern.
[0083] As shown in the figure, in the thermoelectric material powder stage, peaks indicating the presence of elemental antimony were observed near 28.67° and 42.816° in all of Examples 1, 2, and 3, and it is clear that the materials are not in a single phase of Mg3Sb2.
[0084] In addition, when the half-value of the main peak of Mg3Sb2 (25.667°) (the ratio of the height at which the area occupied by the upper side of the target peak is the same as the area occupied by the lower side of the target peak when the target peak is divided into upper and lower parts at a certain height, to the height of the target peak itself) is viewed as the output value of the above-mentioned X-ray diffraction device, it is 0.439 in Example 1 and 0.234 in Examples 2 and 3.
[0085] A larger half-value value (closer to 1) indicates a sharper peak and higher crystallinity, and therefore, comparing Example 1 with Examples 2 and 3, Example 1 has higher crystallinity. As described above, the sintered body of Example 1 has a thermoelectric performance (power factor PF) that is about three times or more higher than that of the sintered bodies of Examples 2 and 3, and this is believed to be due to the high crystallinity of the thermoelectric material powder before sintering. [Explanation of symbols]
[0086] S1 Weighing process S2 mixing process S3 Molding process S4 Synthesis process S5 Crushing process S6 Sintering process S21 Magnesium addition process S22 Mixing process 300 Sintering fixture 301 Mg3Sb2 thermoelectric material 311 Dice 312,313 punch 321 Cylindrical carbon paper 322,323 Carbon paper disc
Claims
1. Mg 3 Sb 2 The raw materials used in the synthesis of Mg-based thermoelectric materials are heat-treated to 3 Sb 2 A synthesis step of synthesizing a thermoelectric material based on the above-mentioned compound, The synthesis step involves heat treatment at a temperature of 300 to 450° C. A method for producing a thermoelectric material comprising the steps of:
2. The heat treatment is performed by holding the temperature for 3 hours. The method for producing a thermoelectric material according to claim 1 .
3. The raw materials are magnesium and antimony. The method for producing a thermoelectric material according to claim 1 or 2.
4. The raw materials are magnesium, antimony, and a dopant. The method for producing a thermoelectric material according to claim 1 or 2.
5. Mg 3 Sb 2 The method further includes a weighing step of weighing the raw materials used in the synthesis of the thermoelectric material. A method for producing the thermoelectric material according to any one of claims 1 to 4.
6. In the weighing step, the composition of the feed is Mg 3+m Sb 2 Weigh out magnesium and antimony so that (0≦m≦0.2) The method for producing a thermoelectric material according to claim 5 .
7. Mg 3 Sb 2 The method further includes a molding step of pressurizing and molding raw materials used in the synthesis of the thermoelectric material. The synthesis step is a step of heat-treating the synthetic green body formed in the molding step to obtain Mg 3 Sb 2 Synthesizing thermoelectric materials based on A method for producing the thermoelectric material according to any one of claims 1 to 6.
8. The thermoelectric material according to any one of claims 1 to 7 is manufactured by the method of producing the thermoelectric material. 3 Sb 2 producing a thermoelectric material based on the The Mg 3 Sb 2 a sintering step of sintering the thermoelectric material; A method for manufacturing a thermoelectric element, comprising:
9. Mg synthesized in the synthesis step 3 Sb 2 The method further includes a grinding step of grinding the thermoelectric material. The sintering step is performed by pulverizing the Mg 3 Sb 2 Sintering of thermoelectric materials The method for manufacturing a thermoelectric element according to claim 8 .
10. The Mg 3 Sb 2 The method further includes a magnesium doping step of doping magnesium to the thermoelectric material; The sintering step is performed by adding magnesium to the Mg 3 Sb 2 Sintering of thermoelectric materials The method for manufacturing a thermoelectric element according to claim 8 or 9.
11. A method for producing a Mg3Sb2-based thermoelectric material, comprising: a synthesis step of synthesizing the Mg3Sb2-based thermoelectric material by heat treatment of raw materials used in the synthesis of the Mg3Sb2-based thermoelectric material; a crushing step of crushing the Mg 3 Sb 2 -based thermoelectric material synthesized in the synthesis step; a magnesium addition step of adding magnesium to the Mg 3 Sb 2 -based thermoelectric material pulverized in the pulverization step; a sintering step of sintering the Mg 3 Sb 2 -based thermoelectric material to which magnesium has been added in the magnesium adding step; Equipped with The synthesis step includes a heat treatment at a temperature below the melting points of magnesium and antimony. A method for manufacturing a thermoelectric element comprising the steps of:
12. In the sintering step, sintering is performed by pressure sintering. The method for manufacturing a thermoelectric element according to any one of claims 8 to 11.
Citation Information
Patent Citations
Novel method for preparing nano-crystallized Mg3Sb2 thermoelectric material
CN107176589A
Hot-press sintering device, block thermoelectric materials of micro-nano porous structure and manufacturing method thereof
CN108963064A
N-type antimony trimagnesium alloy thermoelectric material with high mobility and preparation method thereof
CN109616568A
Magnesium antimony-based thermoelectric element and preparation method and application thereof
CN110635020A
N-type antimonous trimagnetite scandium-doped alloy thermoelectric material and preparation method thereof
CN111057884A